Large seeds of Ormosia paraensis increases germination - Caldas, José Hallef Conceição; Jardim, Iselino Nogueira; Freitas , Alessandra Doce Dias de (Brazilian Journal of Production Engineering, 2024)
Studies related to seed size and its influence on germination can contribute to the selection of seeds with the best attributes for producing healthy and vigor ous seedlings. Thus, the objective of the study was to characterize the dimensions of Ormosia paraensis seeds and evaluate the effect of seed size on the germination process. Intact seeds were classified into two categories: large (≥ 14 mm) and small (< 13 mm). The physical quality of the seeds was evaluated by the number of seeds per kilogram, mass of one thousand seeds, moisture content and biometric measurements (length, width and thickness). The germination test was conducted in a Biolog Oxygen Demand (BOD.) type incubator chamber, at a constant temperature of 30 °C, 12-hour photoperiod, for 15 days. Germination percentage, average time, average speed, germination speed index were evaluated. The statistical design was completely randomized and the means were compared using the Scott-Knott test at 5% probability. The results indicate the existence of significant variation between seed sizes for biometric and seed quality characteristics The results demonstrate that large Ormosia paraensis seeds have the best attributes for producing healthy and vigorous seedlings.
Keywords: Forestry; Propagation; Native species